INOVASI PENGEMBANGAN KETERAMPILAN DIGITAL DAN KEWIRAUSAHAAN KREATIF MELALUI PELATIHAN KOMPUTER DI PKBM INSAN KAMILA - Badru Jaded (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Digital skills and creative entrepreneurship training is an important innovation in improving the quality of non-formal education at PKBM Insan Kamila. This program is designed to equip participants with basic computer skills and entrepreneurship knowledge relevant to current market needs. Interactive and practical learning methods enable participants not only to master digital technology but also to independently develop creative business ideas. The training outcomes are expected to enhance participants' competitiveness in the job market and micro-enterprises, while also supporting the economic empowerment of the surrounding community. This innovation represents a strategic step by PKBM Insan Kamila in addressing the challenges of the digital age and expanding access to quality education for communities not yet reached by formal education.